Channa striata (Ikan Gabus) Extract and the Acceleration of Tuberculosis Treatment: A True Experimental Study - Ma’rufi, Isa; Ali, Khaidar; Sedemen, Ign Arya; Purwanto, P.; Khoiri, Abu (Interdisciplinary Perspectives on Infectious Diseases, 2019)
Tuberculosis is international health problem, which is classified in Global Emergency disease since 1992. The objective of the study is to determine the effect of Channa striata extract toward the acceleration of tuberculosis treatment. The study used true experiment, in which the intervention of the study was Channa striata supplementation to respondent. In addition, Chi-square was used to analyze the data with SPSS version 22. The result is the proportion of respondent classified in negative category in intervention group within week 0, week 1, week 2, week 3, and week 4 being 10.7%, 35.9%, 56.3%, 70.9%, and 90.3%, respectively. Besides, the proportion of respondent classified in negative category in control group within week 0, week 1, week 2, week 3, and week 4 was 13.4%, 23.7%, 37.1%, 49.5%, and 68%, respectively. Based on Chi-square test, the P value of Channa striata supplementation toward the acceleration of tuberculosis treatment week 1, week 3, and week 4 is 0.045, 0.019, and 0.005 (P< α; α=0.05), respectively. It means that there were differences between Channa striata supplementation and acceleration of tuberculosis treatment among respondent. Therefore, Channa striata treatment was significantly related to the acceleration of tuberculosis recovery.